16S rRNA GENE BASED IDENTIFICATION OF GUT BACTERIA FROM LABORATORY AND WILD LARVAE OF HELICOVERPA ARMIGERA (LEPIDOPTERA: NOCTUIDAE) FROM TOMATO FARM - S. MADHUSUDAN; S. K. JALALI; T. VENKATESAN; Y. LALITHA; R. PRASANNA SRINIVAS (The Bioscan, 2011)
Tomato fruit borer Helicoverpa armigera (Hübner) is a polyphagous pest of different host plants and has developed resistance to most of the insecticide groups. In order to know the gut microbial flora of the wild and laboratory larvae of H. armigera, whole gut was dissected from the fourth to fifth instar wild and laboratory larvae of the H. armigera and the culturable bacterial species were identified by sequence analysis of 16S rRNA gene. Altogether eleven bacterial species of different genera were identified from wild populations were Stenotrophomonas sp., Enterococcus casseliflavus, Enterococcus sp., Enterococcus gallinarum, Enterococcus feacium, Bravundimonas diminuta, Staphylococcus sp., Pseudomonas aeruginosa, Acinetobacter calcoaceticus, Bacillus subtilis and Rhodococcus sp., of which genera Enterococcus were found to be predominant and the bacterial species from laboratory populations were Proteus vulgaris, Cellulosimicrobium cellulans, Klebsiella oxytoca, Bacillus subtillis, Stenotrophomonas maltophilla and Pseudomonas sp., which showed variation in the bacterial sp., in laboratory and wild populations. The nucleotide sequences of 11 isolates from wild and 6 isolates from laboratory populations were submitted to NCBI-GenBank and accession numbers was obtained